Franklin in the dark - Bourgeois, Paulette; Clark, Brenda (Toronto : Kids Can Press, 1986)
A turtle afraid of small dark places, and therefore of crawling into his shell, asks a variety of animals for advice, only to find out that each has a fear of its own.
2.3
K-3
Keywords: Animals -- Fiction; Fear -- Fiction; Turtles -- Fiction; Animals -- Fiction; Fear -- Fiction; Turtles -- Fiction